Accounting conservatism, Islamic social reporting, and earning responses coefficient: An empirical analysis - Embuningtyas, Sandra Sukma; Anggraeni , Rani; Puspasari, Oktaviani Rita (IAIN Surakarta, 2022)
This research aims to determine the influence of accounting conservatism, sharia-based social performance disclosure and company size both partially and simultaneously against earnings response (earnings response coefficient). Empirical study of Sub- sector property and Real Estate companies registered in ISSI on Indonesia Stock Exchange period 2015-2018. The method used is descriptive and verification method with quantitative data. The data collection technique used non-participating observation. The results concluded that partially accounting conservatism was positively and significantly influential on the earnings response, sharia-based social performance disclosure has a positive and significant effect on earnings response, company size positively and significantly affects the earnings response and the simultaneous conservatism of accounting, sharia-based social performance disclosure and company size together have a positive and significant impact on the earnings response.